PV Isolation Using a Spherical Array PFA Catheter: Application Repetition and Lesion Durability (PULSE-EU Study) - Turagam, Mohit K; Neuzil, Petr; Petru, Jan; Funasako, Moritoshi; Koruth, Jacob S; Reinders, Daniel; Skoda, Jan; Kralovec, Stepan; Reddy, Vivek Y (JACC. Clinical electrophysiology, 2023)
BACKGROUND: Preclinical studies have revealed that pulsed field ablation (PFA) lesion dimensions increase with repetitive applications at a similar electric field. OBJECTIVES: This study investigated whether pulmonary vein isolation (PVI) durability varies with single vs repetitive pulsed field (PF) applications. METHODS: Atrial fibrillation patients underwent PVI using a spherical multielectrode array PFA catheter delivered with a 19-F deflectable sheath under intracardiac echocardiographic guidance. Esophagogastroduodenoscopy and brain magnetic resonance imaging were performed within 1 to 3 days, and invasive remapping at ∼2 to 3 months. RESULTS: The patient cohort (n = 21; age 63 ± 11 years; 67% women) underwent PVI in either of 2 groups: group 1 (n = 11)-single PF application/PV; and group 2 (n = 10)-3 PF applications/PV. In both groups, PVI was acutely successful in all (100%) patients. Despite significantly longer pulse delivery times (75.2 ± 7.4 s/patient vs 24.5 ± 5.5 s/patient) the procedure times (73.2 ± 13.7 minutes vs 93.7 ± 18.5 minutes) were shorter with group 2 vs group 1. There was no stroke/transient ischemic attack, pericardial effusion, phrenic nerve injury, or esophageal complications. Esophagogastroduodenoscopy was normal in both groups of patients (n = 9). Screening brain magnetic resonance imaging revealed asymptomatic cerebral lesions (diffusion weighted imaging+/fluid attenuated inversion recovery-) in 3 of 16 (18.7%) patients. PV remapping revealed durable PVI in 62.5% PVs in group 1 (n = 10), compared with all 100% PVs in group 2 (n = 9); this translates to all PVs being durably isolated in 30% vs 100% (P < 0.05) of patients in groups 1 and 2, respectively. CONCLUSIONS: In his first-in-human trial, the "single-shot" spherical array PFA catheter was shown to safely isolate PVs. Repetitive PF application is key for lesion consolidation to maximize PVI durability.
Keywords: výsledek terapie; Male; atrial fibrillation; Heart Rate; catheter ablation; Aged; Catheters; pulmonary vein isolation; mužské pohlaví; senioři; srdeční frekvence; pulse field ablation; Catheter Ablation; Pulmonary Veins; Treatment Outcome; Time Factors; katétry; lidé; ženské pohlaví; Humans; časové faktory; venae pulmonales; katetrizační ablace; Female; lidé středního věku; Middle Aged